Artificial Intelligence (AI) in Islam: Building Ethics and Solutions Based on Tawhid - Mamdukh Budiman; Mirza Mahbub Wijaya; Rijal Wakhid Rizkillah; Iqbal Hidayatsyah Noor; Safuan Safuan; Rachmat Destriana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article explores the application of Islamic ethics, particularly the concept of tawhid, in the development of digital technologies and artificial intelligence (AI). The study employs a qualitative descriptive method based on a literature review to analyze Islamic principles, such as justice (al-'adl), trust (amanah), and public benefit (al-maslahah), in addressing ethical challenges posed by AI. The findings indicate that Islamic values can provide a holistic framework for tackling algorithmic bias, privacy concerns, and social inequalities associated with AI. However, the study identifies a gap in academic research regarding the integration of tawhid principles with AI development. A limitation of this research is the lack of empirical case studies to test the effectiveness of implementing these principles in technology development.